Effect of synthesis conditions on the structure and properties of LiFeO2/ZnFe2O4 nanocomposites prepared by a sol-gel method. (August 2021) - Chang, Sun; Mei, Sun; qianqian, Ren; Yang, Li; Yang, Li; Lu, Zhang; Shuang, Wu; Wen, Guo
Abstract: A series of LiFeO2 /ZnFe2 O4 nanocomposites with different LiFeO2 contents were successfully synthesized from LiOH·H2 O, Zn(NO3 )2 ·6H2 O and Fe(NO3 )3 ·9H2 O by a sol-gel method at various calcination temperature. The effect of composition and calcination temperature on structural and electromagnetic properties was studied by means of x-ray diffraction (XRD), scanning electron microscopy (SEM) and vector network analyzer. The XRD results indicated that the existence of LiFeO2 and ZnFe2 O4 phase. SEM results showed that the prepared powder reveals irregular particle shapes and random particle size. Electromagnetic property results revealed that the minimum reflection loss and the frequency bandwidth of microwave absorption can be adjusted by changing the composition of the prepared composites. It is also proposed that the sol-gel method is an effective way to prepare the multiphase materials with adjustable properties. Highlights: A series of LiFeO2 /ZnFe2 O4 nanocomposites with different LiFeO2 contents were successfully synthesized by a sol-gel method. Average crystallite size of LiFeO2 and ZnFe2 O4 phase of 55LZ 10/5 sample is 26.1, and 21.2 nm respectively. The effect of composition and calcination temperature on structural and electromagnetic properties was studied. The sol-gel method is an effective way to prepare the multiphase materials with adjustable properties.